Mineralogy of various types of Th-U-REE mineralisation in the iron oxide – apatite deposits of the Bafq district, Central Iran. Issue 1 (2nd January 2023) - Khoshnoodi, Khalegh; Ziapour, Samaneh; Yazdi, Mohammad; Cuney, Michel
ABSTRACT: The Bafq district, well-known in the world, is the most important iron province in Central Iran. The Early Cambrian volcano-sedimentary sequence in this district, hosts a lot of mineral deposits such as Kiruna-type iron oxide-apatite (IOA), Fe-Mn exhalative and Pb-Zn SEDEX types. Th-U-REE mineralisation in the Bafq IOA deposits occurs in a variety of element associations, (i) REE-P mineralisation as apatite hosting REE-mineral inclusions, (ii) Th-REE mineralisation as Th-REE minerals (e.g. REE-bearing thorite and titanite), (iii) thorium mineralisation as thorium minerals (e.g. thorite and huttonite), (iv) U-REE mineralisation as U-REE minerals (e.g. uraninite and cleveite) and (v) REE-U-Th mineralisation as REE-U-Th minerals (e.g. davidite and allanite). Two main types of apatite are recognised: apatite with inclusions (dominantly monazite, xenotime and allanite) and inclusion poor/free apatite. The presence of calcite paragenesis with Th-REE, Th and U-Th-REE mineralisation indicates transportation of Th and REEs by carbonate complexes in post-magmatic alkaline fluids.